The Role of Geographic Information Science in Achieving Sustainable Development Goals (SDGs) During The Covid-19 Pandemic - Annisa Joviani Astari; Assem Abdelmonem Ahmed Mohamed; Riki Ridwana (Jurnal Pendidikan Geografi Gea, 2021)
Sustainable development and the goals that have been set by the UN are the results of mutual agreement on various pressing issues that must be addressed by our society. Along with the pandemic conditions that hit various parts of the world, the challenges for the realization of sustainable development are getting higher. Geospatial technology offers reliable tools to support the various processes and stages of planning, analysis, problem-solving, decision making, and process management necessary to pursue this common goal. GIScience has a very important role in investigating opportunities to help solve sustainable development problems. This study presents the state of the art of how GIScience plays a role to achieve sustainable development goals particularly during pandemic covid situations which resulting in a backward for some actors in several countries to achieve these goals. This study uses the content analysis method to analyze various issues related to sustainable development, SDGs, pandemic covid-19, and GIScience. Not only providing state of the art of research, but this paper also presents how actually GIScience can help to accelerate the problems thus the ultimate goal of sustainability can be achieved.